Comicidade e diversidade: a espetacularidade da quadrilha cômica Close Junino do bairro de Canudos nas ruas de Belém-PA - MATOS, Fábio Henrique Cardoso de (2023)
The present study analyzes the Brazilian comical square dance “Close Junino” in Canudos, Belém-PA. I have experiences in the june festivals since I was kid, because I have Always had the practice, such as, my artistic career in the Brazilian square dance, investigating the diversity and the comical as popular manifestation, on the streets of Belém, without losing the essence and the traditionality of June Festivals, emphasizing the dance with the LGBTQIA+ people. The qualitative approach was realized through my experience as artist, researcher and performer, with my group of Brazilian square dance and Other comical groups. In this way, it was necessary to realize interviews on social media, field research, practices and the performance observation over the years, the basic theoretical framework was centered on Ethnocenology, which I learned in the subject “Brazilian Spectacular Manifestations I and II”, of Degree course in Dance – UFPA. In this way, I used the Ethnocenology studies of Oliveira (2015) and Dumas (2010), and about Brazilian Square Dance, Leal (2004) and Santos (2017). In conclusion, I presente in a preliminar way a historical record of a Brazilian comical square dance and it’s performance, considering that we have little information and records of these dance groups in Belém-PA, to conclude I analyze the Brazilian comical square dance “Close Junino” as choreographer and leader, emphasizing the costumes, dance and creative processes, placing the group as a form of study and as LGBTQIA+ and street art.